In the Absence of Post (Papeles, 2015)
In depth, this paper reports a proposal to build students politically aware and ethically sensitive, through a model (set in the title “Crystals of time”) for a thought that eludes the straitjacket of linearity: it is a mode of focalisation that is particularly called ´post-’. The author privileges the concept of focalisation as the most important in postcolonial narratology and leads the readers to explore how, by understanding both present and absent focalisation, it is possible to discover new imaginative and enriching visions, into a context of an intimate and empathic relationship between an interactive Reading and an interactive reader. The author also looks at the concepts of “gaze” and “iconicity”.
Keywords: Post-; postcolonial narratology; interactive reading; interactive readers; viewer; memories; experiential participation; present focalisation; absent focalisation; interpretation; representation